Online and marketing-based market design - Echenique, Federico; Immorlica, Nicole; Vazirani, Vijay V.; Roth, Alvin E. (New york Cambridge University Press, 2023)
The rich, multi-faceted and multi-disciplinary field of matching-based market design is an active and important one due to its highly successful applications with economic and sociological impact. Its home is economics, but with intimate connections to algorithm design and operations research. With chapters contributed by over fifty top researchers from all three disciplines, this volume is unique in its breadth and depth, while still being a cohesive and unified picture of the field, suitable for the uninitiated as well as the expert.